Vyshyvanka as a Marker of the National Identity of Ukrainians Abroad - Rendiuk, T. (Матеріали до української етнології, 2023)
The article is dedicated to a new topic in Ukrainian and foreign historiography, namely, highlighting the significance and place of Ukrainian vyshyvanka in defining the national identity of tens of millions of Ukrainians abroad. On the background of formation and crystallization of the global Ukrainian ethnic space as a result of the mass emigration of Ukrainian residents to 150 foreign countries because of the full-scale phase of the Russian-Ukrainian war with its single Ukrainian linguistic universe, there is logically an increased scientific interest in studying and highlighting the role of Ukrainian vyshyvanka in the formation and preservation of the national identity of Ukrainians abroad, which explains the relevance of submitted study. The special importance of Vyshyvanka as an indicator of the national identity of Ukrainians abroad is investigated both for the classic diaspora and for the modern, new wave of emigrants provoked by the current Russian military aggression against Ukraine. Particular emphasis is placed on the participation of children of Ukrainians abroad in numerous events on the occasion of World Vyshyvanka Day and calendar holidays, such as St. Nicholas, Christmas, Easter, etc. So, Ukrainian history, culture, and holidays of our compatriots abroad cannot be imagined without Ukrainian vyshyvanka. It is concluded on the basis of the analysis of various factual material of Ukrainian and foreign origin, that vyshyvanka is a deep symbol of national identity, a sign of self-expression of our people, its ethnic brand for Ukrainians. Vyshyvanka is a national symbol uniting those who support their Motherland with their hearts and souls, respect the rich traditions of the Ukrainian people, and glorify priceless cultural heritage on the territory of our country and far beyond its borders. It transmits these national values from the older generations of Ukrainians to the young. This phenomenon ensures the continuity of Ukrainianness throughout the world. Статтю присвячено новій темі у вітчизняній та зарубіжній історіографії, а саме – висвітленню ролі та місця української вишиванки у визначенні національної ідентичності десятків мільйонів закордонних українців. На тлі формування й кристалізації глобального українського етнічного простору як результат масової еміграції мешканців України до 150 зарубіжних країн унаслідок повномасштабної фази російсько-української війни з його єдиним українським мовним всесвітом, логічно виникає і підвищений науковий інтерес до вивчення й висвітлення ролі української вишиванки у формуванні та збереженні національної ідентичності українців зарубіжжя, чим пояснюється актуальність пропонованого дослідження. Досліджено особливу роль вишиванки як індикатора національної ідентичності закордонних українців – як для класичної діаспори, так і для сучасної, нової, хвилі емігрантів, спровокованої нинішньою російською військовою агресією проти України. Окремий наголос робиться на участі дітей закордонних українців у проведенні численних заходів, а саме: Всесвітнього дня вишиванки, Дня святого Миколая, Різдва, Великодня тощо. Отже, українську історію, культуру та свята наших співвітчизників за кордоном неможливо уявити без української вишиванки. На основі аналізу різноманітного фактологічного матеріалу українського та зарубіжного походження зроблено висновок про те, що вишиванка для українців – глибинний символ національної ідентичності, ознака самовираження нашого народу, його етнічний бренд. Вишиванка – це національний символ, що об’єднує тих, хто серцем і душею вболіває за свою Батьківщину, поважає багаті традиції українського народу, прославляє безцінні культурні надбання на теренах нашої країни та далеко за її межами. Вона передає ці національні цінності від старших поколінь українців до молодих, чим забезпечується континуїтет українства в усьому світі.